Linking Stability Conditions and Ore Dilution in Open Stope Mining - Andreas Delentas; Andreas Benardos; Pavlos Nomikos (Materials Proceedings, 2021)
The estimation of the stability conditions, over-breaks, and spalling failures, which could inflict potential external dilution, is a key parameter so as to ensure the optimal design of the exploitation and its cost effectiveness The research undertaken aims at correlating established empirical approaches for the estimation of the stability condition with numerical analysis that identifies and measures the depth of failure. A number of analyses have been conducted and the results obtained yield promising results that can be transformed to direct mathematical expressions applied for the early estimation of dilution rates. Furthermore, through the research, an initial proposal is made for a dilution-based stability graph that could be utilized for the early identification of dilution.